Nasolacrimal intubation in adults. Issue 9 (1st September 1998) - Fulcher, Tim; O'Connor, Martin; Moriarty, Paul
Abstract : BACKGROUND/AIMS: Silicone intubation has been shown to be successful in the management of epiphora in children. The effectiveness of this procedure was assessed in adults. METHODS: 70 eyes from 53 patients underwent nasolacrimal intubation. Mean age at intubation was 54.7 years. Mean follow up period was 15 months. The results were based on improvement of symptoms. RESULTS: Complete resolution of symptoms was reported in 54.3%. A partial improvement was reported in 14.3%, a transient improvement in 10%, and no improvement in 21.4%. A better outcome was associated with canalicular than with nasolacrimal obstructions (complete resolution of symptoms in 75.9% versus 25%). Only 17.1% have subsequently required dacryocystorhinostomies. CONCLUSION: Silicone intubation of the nasolacrimal system is a successful procedure in the management of adult epiphora.